On (1,1,0)-F-Face magic mean labeling of some graphs - Kumari, A. Meena,; Arockiaraj S., (Utilitas Mathematica, 2017)
In this paper, the (1,1,0)-F-Face magic mean labeling of a planar graph is introduced and it is an assignment of labels to the vertices and edges of planar graph such that the mean weight of each face including the exterior face is constant. The (1,1,0)-F-Face magic mean labeling of some planar graphs have been discussed. © 2015 Utilitas Mathematics.